Akutní traumatická hernie intervertebrálního disku - Soukup, J; Černý, J; Novotný, T (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2023)
Acute traumatic intervertebral disc herniation of the thoracic spine is a rather rare injury with only a few reported cases to date. In this manuscript, we present a case of a 58-year-old male patient who sustained a car accident-related high-energy trauma, resulting in a disc herniation of the thoracic spine. Furthermore, we also discuss the possible implications of late diagnosis of such condition. The patient was initially referred from the Emergency Department as a case of head contusion with a left upper limb paresis. Due to only minimal bony trauma visible on the initial spine CT scan, the neurological deficit was attributed to the cranial trauma. The diagnosis of a traumatic disc herniation was therefore established only after the rapid onset of paraparesis, which gradually progressed into paraplegia, and a following spine MRI scan. Despite the subsequent urgent spinal decompression, the neurological functions of the lower limbs were not restored. This manuscript addresses the indications for performing MRI scans in polytrauma patients with a CT-verified spine trauma. Although it may be complicated to perform routine MRI scans in all such patients in daily practice, it can certainly help diagnose such injuries earlier and thus prevent potential permanent neurological damage to the patients. Key word: spine injury, traumatic disc herniation, thoracic spine, spine surgery.
Keywords: Intervertebral Disc Displacement; dolní končetina; Multiple Trauma; chirurgická dekomprese; Lower Extremity; Humans; polytrauma; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; Decompression, Surgical; Emergency Service, Hospital; urgentní služby nemocnice; výhřez meziobratlové ploténky